2007
DOI: 10.1136/gut.2006.092460
|View full text |Cite
|
Sign up to set email alerts
|

Adenovirus-mediated expression of BMP-7 suppresses the development of liver fibrosis in rats

Abstract: Background: Liver cirrhosis, which is caused by the accumulation of extracellular matrix materials, is a serious clinical problem that can progress to hepatic failure. Transforming growth factor-b (TGFb) plays a pivotal role in extracellular matrix production, but bone morphogenetic protein (BMP)-7, a member of the TGFb superfamily, can antagonise the fibrogenic activity of TGFb. Aim: In this study, we examined whether adenovirus-mediated overexpression of BMP-7 (Ad-BMP-7) antagonised the effect of TGFb in vit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
110
0
5

Year Published

2007
2007
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(125 citation statements)
references
References 48 publications
8
110
0
5
Order By: Relevance
“…Upon BMP7 administration they observed a decrease in fibrotic lesions and improved liver function as determined by the analysis of albumin serum levels [122]. In the same line of evidence, it has been reported that adenovirus-mediated expression of BMP7 reduces liver fibrosis in rats, but the mechanism of this effect was not determined [123]. BMP7 protective properties in liver injuries have been also supported by evidence suggesting that endogenous BMP7 enhances regeneration of liver mass after partial hepatectomy being therefore a physiological regulator of hepatocyte proliferation and function [5].…”
Section: Bmps In Liver Fibrosissupporting
confidence: 56%
“…Upon BMP7 administration they observed a decrease in fibrotic lesions and improved liver function as determined by the analysis of albumin serum levels [122]. In the same line of evidence, it has been reported that adenovirus-mediated expression of BMP7 reduces liver fibrosis in rats, but the mechanism of this effect was not determined [123]. BMP7 protective properties in liver injuries have been also supported by evidence suggesting that endogenous BMP7 enhances regeneration of liver mass after partial hepatectomy being therefore a physiological regulator of hepatocyte proliferation and function [5].…”
Section: Bmps In Liver Fibrosissupporting
confidence: 56%
“…BMP-7 targets mesangial cells in kidney and hepatic stellate cells in liver that are key mediator cells during fibrogenesis. Moreover, it has been shown in both cell types that BMP-7 directly interferes with profibrogenic TGF-␤1 signaling (57,64). Because endoglin is also expressed by mesangial and hepatic stellate cells (43,65), it is tempting to speculate that endoglin is a critical modifier of fibrogenic responses.…”
Section: Discussionmentioning
confidence: 99%
“…In the light of fibrogenic processes, the finding that endoglin is a modifier of BMP-7 signaling is very interesting. In experimental models of kidney fibrosis and liver fibrosis, the administration of BMP-7 resulted in resolution of fibrosis (63,64). BMP-7 targets mesangial cells in kidney and hepatic stellate cells in liver that are key mediator cells during fibrogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies, however, have convincingly used components of either collagen ␣(1)I, collagen ␣2(I), or ␣-SMA promoters to direct transgene expression in activated stellate cells (311,312,367). More challenging has been the identification of transgenic promoters to ectopically express genes in quiescent stellate cells.…”
Section: Other Models: Liver Slices In Vivo Methodsmentioning
confidence: 99%